Bidirectional regulation between 1st trimester HTR8/SVneo trophoblast cells and in vitro differentiated Th17/Treg cells suggest a fetal‐maternal regulatory loop in human pregnancy. (11th April 2019) - Wang, Songcun; Qian, Jinfeng; Sun, Fengrun; Li, Mengdie; Ye, Jiangfeng; Li, Mingqing; Du, Meirong; Li, Dajin
Abstract : Problem: During normal pregnancy, delicate crosstalk is established between fetus‐derived trophoblasts and maternal immune cells to ensure maternal‐fetal tolerance and successful placentation. Dysfunction in these interactions has been highly linked to certain pregnancy complications. Method of study: Naïve CD4 + T cells were cultivated with or without 1st trimester derived trophoblast cell line HTR8/SVneo cells in the absence or presence of T helper 17 (Th17) or regulatory (Treg)cell‐inducing differentiation conditions. After 5 days of co‐culture, HTR8/SVneo cells and CD4 + T cells were harvested and analyzed using flow cytometry . Results: CD4 + T cells exposed to HTR8/SVneo cells showed enhanced induction of CD4 + Foxp3 + Treg cells with strong expression of TGF‐β1 and inhibitory molecules (cytotoxic T lymphocyte‐associated protein‐4 [CTLA‐4], T‐cell immunoglobulin mucin‐3 [Tim‐3], and programmed cell death‐1 [PD‐1]). Though not effecting Th17 differentiation, exposure to HTR8/SVneo cells promoted increased expression of proliferative and apoptotic markers on Th17 cells. Co‐culture with Th0 cells, or differentiated Th17 or Treg cells, down‐regulated Caspase‐3 and MMP‐9 (but not MMP‐2) expression in HTR8/SVneo cells, while promoting Ki67 expression. Conclusions: HTR8/SVneo cells regulated maternal CD4 + T‐cell differentiation, resulting in the expansion of immunosuppressive Treg cells, while CD4 + T cells might promote the growth, and control the invasiveness of HTR8/SVneo cells. Thus, a bidirectional regulatory loop might exist between trophoblasts and maternal immune cell subsets, thereby promoting harmonious maternal‐fetal crosstalk.